The dark and the bright side of power: implications for the management of business-to-business relationships - Vera Belaya; Jon Henrich Hanf (Agricultural and Food Economics, 2016)
The importance of power is underlined by many scientists who view it as a key behavioral construct. Power distinguishes itself as an effective tool in coordinating and promoting harmonious relationships, solving conflicts, and enhancing performance. An important challenge is to determine what role power plays in managing businessto-business relationships with specific attention to coordination and cooperation. The aim of our work is to investigate the role of power in business-to-business relationships to work out a strategy that enables managers to select an effective mix of power mechanisms. We work out and test a theoretical model of the effects of power on cooperation and coordination in business-to-business relationships and discuss possible managerial implications. To verify our research hypotheses, we conduct expert interviews via telephone about relationships of international food processing companies with their suppliers in Russia.
Keywords: 330; Business-to-business relationships; Supply chain management; Power; Focal company